Методика исследования коллизионных свойств кодов аутентификации сообщений - Кузнецов, Александр Александрович; Король, Ольга Григорьевна; Босько, В. В.; Евсеев, Сергей Петрович (Національна академія сухопутних військ ім. гетьмана Петра Сагайдачного, 2011)
Рассматривается схема формирования кодов аутентификации сообщений, основанная на использовании универсального хеширования (UMAC - Message Authentication Code using Universal Hashing). Предлагается методика статистического исследования коллизионных свойств UMAC. В основе предлагаемой методики лежит использование уменьшенной модели кодов аутентификации сообщений (мини-UMAC), построенной посредством масштабирования применяемых преобразований с сохранением их алгебраической структуры.

A scheme of the shaping the codes of messages authentification, based on UMAC - Message Authentication Code using Universal Hashing is considered. A method of statistical study of UMAC collision characteristics is offered. Employment of reduced model of message authentification codes (mini-UMAC), built by means of scaling the applied transformations with conservation of their algebraic structure serves as a base for the proposed method.
Methods of collision characteristic research of the message authentification codes
Keywords: коды аутентификации сообщений; коллизионные свойства; аутентификация; МАС-код; UMAC; message authentification codes; collision characteristics; authentification; MAC-code